ANALISIS OPTIMALISASI PERENCANAAN PAJAK PENGHASILAN DALAM RANGKA PENGHEMATAN ARUS KAS KELUAR - Iswandir Iswandir (JURNAL MITRA MANAJEMEN, 2016)
ABSTRACT This study aimed to analyze the outflow of savings as a result of optimization ofincome tax planning of the company research method used is descriptive method.This method in accordance with the purpose of this study was to depict or describethe properties of a situation and seek answers to the problems that have beenidentified in parts of the formulation of the problem. The results of this studyshowed that companies need to optimize the planning of income tax on the postsof income and expense, so the taxable income to be paid by the company to besmaller than it should be. After analysis of tax planning by the author based on theRule of Law taxation, companies can save on tax payments in a way that is legal.Keywords: Tax, Income Tax Planning.